Adiponectin Attenuates Lipopolysaccharide-induced Apoptosis by Regulating the Cx43/PI3K/AKT Pathway - Liu, Luqian; Yan, Meijuan; Yang, Rui; Qin, Xuqing; Chen, Ling; Li, Li; Si, Junqiang; Li, Xinzhi; Ma, Ketao (Frontiers in Pharmacology, 2021)
Cardiomyocyte apoptosis is a crucial factor leading to myocardial dysfunction. Adiponectin (APN) has a cardiomyocyte protective impact, but the mechanism is unclear. Our study aimed to confirm whether APN protects against LPS-induced cardiomyocyte apoptosis and to explore the underlying mechanism. In vitro experiments: Before H9c2 cells were treated with LPS for 24 hours, they were pre-treated with APN for 2 hours. The function of APN on H9c2 cells cytotoxicity was evaluated by CCK-8 assay. The protein levels of Bax, Bcl2, cleaved caspase-3, cleaved caspase-9, connexin43 (Cx43), PI3K, p-PI3K, AKT and p-AKT were evaluated by Western blot, and the apoptosis rate was evaluated by flow cytometry. The results indicated that LPS upregulated Bax, cleaved caspase-3 and cleaved caspase-9 and downregulated Bcl2 in H9c2 cells; however, these effects were attenuated by APN. APN downregulated the Cx43 level and activated the PI3K/AKT signalling pathway. LPS induced apoptosis in H9c2 cells, and these effects were attenuated by Gap26 (Cx43 inhibitor). Gap26 activated the PI3K/AKT signalling pathway. Moreover, the preservation of APN was reversed by LY294002 (PI3K/AKT signal pathway inhibitor). In vivo experiments: In C57/BL6J mice, the sepsis model was constructed by intraperitoneal injection of LPS and APN was injected in enterocoelia. The protein levels of Bax, Bcl2, cleaved caspase-3, Cx43 were evaluated by Western blot and Immunohistochemistry was used to detect Cx43 expression and localization in myocardial tissue. The results indicated that LPS upregulated Bax, cleaved caspase-3, Cx43 and downregulated Bcl2 in sepsis; however, these effects were attenuated by APN. APN downregulated the Cx43 level. In conclusion, the data demonstrate that APN can protect sepsis against LPS-induced apoptosis by modifying the Cx43/PI3K/AKT signalling pathways.